NFAT1 and NFAT2 Differentially Regulate CTL Differentiation Upon Acute Viral Infection - Xu, Tianhao; Keller, Ashleigh; Martinez, Gustavo J. (Frontiers in Immunology, 2019)
CD8+ T cell differentiation orchestrated by transcription regulators is critical for balancing pathogen eradication and long-term immunity by effector and memory CTLs respectively. The transcription factor Nuclear Factor of Activated T cells (NFAT) family members are known for their roles in T cell development and activation but still largely undetermined in CD8+ T cell differentiation in vivo. Here, we interrogated the role of two NFAT family members, NFAT1 and NFAT2, in the effector and memory phase of CD8+ T cell differentiation using LCMVArm acute infection model. We found that NFAT1 is critical for effector population generation whereas NFAT2 is required for promoting memory CTLs in a cell intrinsic manner. Moreover, we found that mice lacking both NFAT1 and NFAT2 in T cells display a significant increase in KLRG1hi CD127hi population and are unable to clear an acute viral infection. NFAT-deficient CTLs showed different degrees of impaired IFN-γ and TNF-α expression with NFAT1 being mainly responsible for IFN-γ production upon ex-vivo stimulation as well as for antigen-specific cytotoxicity. Our results suggest that NFAT1 and NFAT2 have distinct roles in mediating CD8+ T cell differentiation and function.